Grammars with context conditions and their applications - Meduna, Alexander (John Wiley & Sons, 2005)
This advanced computer science book systematically and compactly summarizes the current knowledge about grammars with context conditions-an important area of formal language theory. According to the types of context conditions, this self-contained reference classifies them into grammars with context conditions placed on the domains of grammatical derivations, the use of grammatical productions, and the neighborhood of the rewritten symbols. The focus is on grammatical generative power, important properties, simplification, reduction, implementation, and applications, most of which are related to microbiology.